Molecular cloning, characterization, and expression of two TNFRs from the pearl oyster Pinctada fucata martensii. Issue 98 (March 2020) - Wu, Yuyuan; He, Junjun; Yao, Gaoyou; Liang, Haiying; Huang, Xuemin
Abstract: Proteins in the tumor necrosis factor receptor (TNFR) superfamily play significant roles in many physiological and pathological events, such as inflammation, apoptosis, autoimmunity, and organogenesis. Here, two TNFR gene homologs ( PmTNFR1 and PmTNFR5 ) were identified in the pearl oyster Pinctada fucata martensii. The predicted PmTNFR1 and PmTNFR5 protein sequences were 406 and 533 amino acids long, respectively, and both possessed motifs characteristic of the TNFR family, including a TNFR homology domain (CRD), a transmembrane domain (TM), and death domains. However, the predicted amino acid sequences of PmTNFR1 and PmTNFR5 had low identity (~16–23%) with sequences of vertebrate TNFR family proteins. Furthermore, PmTNFR5 had a death domain at the C-terminal, indicating that this protein may be a novel member of the TNFR superfamily. Constitutive PmTNFR1 and PmTNFR5 mRNA expression was detected in all six pearl oyster tissues tested, with comparatively greater transcript abundance in the hepatopancreas and gill. The gene expression levels of PmTNFR1 and PmTNFR5, as well as those of downstream signaling molecules related to the NF-κB pathway ( RIP, TRAF2, TRAF3, IKK, and NF-κB ), were quantified in the gill after LPS challenge and in the hemocytes after nucleus insertion surgery using real-time PCR (qRT-PCR). We found that all genes were significantly upregulated at 6 h and 12 h post-injection, as well as at 15 d post-insertion. We used RNAi to inhibit the expression of the PmTNFR1 and PmTNFR5 genes. We then quantified the expression levels of PmTNFR1 and PmTNFR5, as well as downstream genes, using qRT-PCR. We found that RNAi inhibition of PmTNFR1 and PmTNFR5 downregulated the downstream genes ( RIP, TRAF2, TRAF3, IKK, and NF-κB ). Therefore, our results suggested that PmTNFR1 and PmTNFR5 mediate the NF-κB signaling pathway, and are closely related to immune defense, particularly allograft immunity, in the pearl oyster P. fucata martensii . Highlights: PmTNFR1 and PmTNFR5 genes were characterized firstly from Pinctada fucata martensii. The expression levels in various tissues after LPS challenge or nucleus insertion surgery were detected, respectively. RNAi was used to inhibit the expression of the PmTNFR1 and PmTNFR5 genes. The NF-κB signaling pathway may be activated by PmTNFR1 and PmTNFR5.